Impact of antimicrobial stewardship and rapid microarray testing on patients with Gram-negative bacteremia - K. R. Rivard; V. Athans; S. W. Lam; S. M. Gordon; G. W. Procop; S. S. Richter; E. Neuner (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Critically reduced frost resistance of Picea abies during sprouting could be linked to cytological changes - G. Neuner; B. Beikircher (Protoplasma, 2010)

Cold-loving microbes, plants, and animals—fundamental and applied aspects - R. Margesin; G. Neuner; K. B. Storey (The Science of Nature, 2007)

Ice formation and foliar frost resistance in attached and excised shoots from seedlings and adult trees of Nothofagus menziesii - G. Neuner; P. Bannister; W. Larcher (New Zealand Journal of Botany, 1997)
Freezing in leaves of N menziesii was monitored by experimental freezing of attached twigs and seedlings growing naturally in a forest site and compared with a routine laboratory test in which excised plant material was used. Major differences in ice nucleation were observed: ice formed in attached leaves in situ at temperatures that were on average 4°C higher than in excised leaves, in both seedlings and adult trees. Excision did not affect the symptoms of frost damage. Mean foliar frost resistance was 2°C lower in seedlings than in mature shoots, and about 1°C lower in shoots measured in situ than in excised shoots.